Intelligent Vehicle Number Plate Recognition System Using Yolo For Enhanced Security In Smart Buildings - Muhammad Adnan Kaim Khani; Muhammad Usama; Abdul Salam Shah; Asadullah Shah; Syed Hyder Abbas; Adil Maqsood; Asif Ali Laghari (Journal of ICT, Design, Engineering and Technological Science, 2024)
The demand for advanced security solutions has increased with the continuous growth of urban infrastructure; hence, automated surveillance systems are vital across universities, hospitals, and commercial spaces. This project proposes an end-to-end Automatic Number Plate Recognition (ANPR) system to identify vehicle license plates by capturing high-speed images under optimal lighting conditions, isolating and analyzing plate characters, and translating the visual data into machine-readable text. By deploying these models on embedded systems, the system uses Convolutional Neural Networks (CNNs) and YOLO (You Only Look Once) for real-time object detection and recognition. The solution leverages the power of edge computing to achieve high performance and low latency for effective vehicle monitoring, data logging, and enhancing overall security infrastructure in buildings.